Antidiabetic drugs. (March 2016) - Waring, W Stephen
Abstract: Over recent years, there has been a rapid expansion of different classes of antihyperglycaemic drugs with diverse toxicological profiles. Insulin and sulfonylurea overdose can cause significant hypoglycaemia, which is reversed by administration of intravenous glucose 10–20%, aiming to achieve a target plasma glucose concentration of ≥4 mmol/litre. However, glucose alone is a potent stimulus for additional insulin release in sulfonylurea-poisoned patients and can result in recurrent and prolonged rebound hypoglycaemia. Octreotide inhibits the secretion of insulin from the pancreas and, when used in sulfonylurea poisoning, is associated with a marked reduction in hypoglycaemic episodes and glucose requirements.